PENGEMBANGAN MEDIA TANGGA KEBIJAKSANAAN UNTUK PEMBELAJARAN PENJUMLAHAN BAGI ANAK KESULITAN BELAJAR MATEMATIKA - Ringga Sary Oktavia (Universitas Negeri Padang, 2015)
Abstract This research was motivated by the problems that have found in SD Rayon III Cluster VI District of Guguak. The students can not add two rows digid down . Researchers want to overcome these problems by creating a media is Wisdom Ladder Media . This study used a Research and Development with Mann Whitney U test . Based on the results of the study proved that the success of the development of media Wisdom Ladder improve the ability summation of children’s mathematics learning difficulties.